2015
DOI: 10.1097/jto.0000000000000691
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Model to Predict Mortality among Non–Small-Cell Lung Cancer Patients in the U.S. Military Health System

Abstract: Introduction Accurate prognosis assessment after non-small cell lung cancer (NSCLC) diagnosis is an essential step for making effective clinical decisions. This study is aimed to develop a prediction model with routinely available variables to assess prognosis in patients with NSCLC in the U.S. Military Health System. Methods We used the linked database from the Department of Defense’s Central Cancer Registry (CCR) and the Military Health System Data Repository (MDR). The dataset was randomly and equally spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
1
12
0
1
Order By: Relevance
“…Few DSS have been developed in patient populations with mixed treatment options, but have not been externally validated, such as the Daniele score [ 63 ], Lin score [ 64 ] and Zhang score [ 65 ]. Only the Blanchon model [ 66 ] has been validated in another population [ 67 ], thereby, reaching Reilly level 2.…”
Section: Resultsmentioning
confidence: 99%
“…Few DSS have been developed in patient populations with mixed treatment options, but have not been externally validated, such as the Daniele score [ 63 ], Lin score [ 64 ] and Zhang score [ 65 ]. Only the Blanchon model [ 66 ] has been validated in another population [ 67 ], thereby, reaching Reilly level 2.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are in agreement with previous reports on risk factors for NSCLC. [9, 14, 27, 3033] Nonsmoking history has been identified as a prognostic indicator in many studies. [3436] Our results revealed that for patients with either EGFR mutation positive or wild-type, the association between smoking status and survival remains significant in the presence of strong predictors, such as treatment and ECOG performance scores.…”
Section: Discussionmentioning
confidence: 99%
“…The association between diabetes mellitus and survival in lung cancer patients is controversial [ 23 ] Whereas some studies suggest that patients with diabetes mellitus have worse prognoses due to comorbidities and disease complications that can be related to a reduced tolerance of treatment [ 24 , 25 ], other studies have demonstrated that diabetic patients exhibited increased survival compared with non-diabetics [ 7 , 26 , 27 ]. The contradictory results between different studies might be the consequence of the analyses of heterogeneous populations.…”
Section: Discussionmentioning
confidence: 99%